A Methodology For Ontology Reuse: The Case Of The Abdominal Ultrasound Ontology - Zulkarnain, Nur Zareen; Meziane, Farid (IGI Global, 2019)
There is an abundance of existing biomedical ontologies such as the National Cancer Institute Thesaurus and the Systematized Nomenclature of Medicine-Clinical Terms. Implementing these ontologies in a particular system however, may cause unnecessary high usage of memory and slows down the systems’ performance. On the other hand, building a new ontology from scratch will require additional time and efforts. Therefore, this research explores the ontology reuse approach in order to develop an Abdominal Ultrasound Ontology by extracting concepts from existing biomedical ontologies. This article presents the reader with a step by step method in reusing ontologies together with suggestions of the off-the-shelf tools that can be used to ease the process. The results show that ontology reuse is beneficial especially in the biomedical field as it allows for developers from the nontechnical background to build and use domain specific ontology with ease. It also allows for developers with technical background to develop ontologies with minimal involvements from domain experts.